Returns to education and wage inequality in Namibia: A gendered analysis - Obrein Muine Samahiya; Ebenezer Lemven Wirba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper estimates the returns to education and their implications for wage inequality using data from the 2015/16 Namibia Income and Expenditure Survey. The paper employs recentred influence function regression to analyse the impact of education across the wage distribution and uses a simulation approach to assess the impact on wage inequality of educational equalization. The results indicate higher returns to education among women compared with men. The quantile results further reveal that within the sample of women, higher returns to education are observed at the lower percentile compared with the upper end of the distribution, while within the sample of men, higher returns to education are observed at the upper end of the wage distribution. Simulation results suggest that educational expansion substantially widens inequality relative to equalization efforts for both men and women. The policy implications include the need to prioritize reducing educational disparities and ensuring equal access to quality education. Targeted interventions should address the specific needs of disadvantaged groups, such as women and individuals from lower-income households, by improving educational quality and supporting vocational training.
Keywords: J24; C21; I26; D31; 330; returns to education; wage inequality; educational equalization; educational expansion; Namibia